2022
DOI: 10.1088/1361-6528/aca3af
|View full text |Cite
|
Sign up to set email alerts
|

Tuning of the electronic and vibrational properties of epitaxial MoS2 through He-ion beam modification

Abstract: Atomically thin transition metal dichalcogenides (TMDs), like MoS2 with high carrier mobilities and tunable electron dispersions, are unique active material candidates for next generation opto-electronic devices. Previous studies on ion irradiation show great potential applications when applied to two-dimensional (2D) materials, yet are limited to micron size exfoliated flakes or smaller. To demonstrate the scalability of this method for industrial applications, we report the application of relatively low powe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 66 publications
0
3
1
Order By: Relevance
“…Figure 6.7 shows the accumulated normalized PL signal intensities for different treatment times at fixed energy of 5 KeV as a function of emission wavelength.In this graph can be observed the emission peak varies slightly from one sample to another, but its overall shape is preserved. This observation contrasts what was observed by Parida et al[53], where they observed the apparition of a new bound exciton while the pristine emission was quenched, possibly due to higher ion dose and energy applied. The graph in figure6.7 by itself might lead one to think the Ion Beam treatment is causing considerable peak emission wavelength shifts.…”
contrasting
confidence: 99%
See 2 more Smart Citations
“…Figure 6.7 shows the accumulated normalized PL signal intensities for different treatment times at fixed energy of 5 KeV as a function of emission wavelength.In this graph can be observed the emission peak varies slightly from one sample to another, but its overall shape is preserved. This observation contrasts what was observed by Parida et al[53], where they observed the apparition of a new bound exciton while the pristine emission was quenched, possibly due to higher ion dose and energy applied. The graph in figure6.7 by itself might lead one to think the Ion Beam treatment is causing considerable peak emission wavelength shifts.…”
contrasting
confidence: 99%
“…Figure 3.3 PL spectra of MoS 2 irradiated by 4 He + ion beams with different fluences given in displacements per atom (dpa) show emergence of the bound exciton, X b , peak around 1.7 eV upon irradiation attributed to generation of point lattice defects. Spectra are shown normalized to the intensity of sapphire peaks and were recorded at 4 K. Adapted from [53]. The tubular furnace used to grow the samples and its controller.…”
Section: List Of Figuresmentioning
confidence: 99%
See 1 more Smart Citation
“…A photoluminescence map was recorded from the same molybdenum sample area ( Figure 6 a). It shows significant quenching for multilayer ( Figure 6 b, blue spectrum) and bulk ( Figure 6 b, cyan spectrum) MoS 2 , not only due to the gradual transition from the monolayer direct bandgap to the bulk indirect bandgap [ 46 , 47 , 48 ], but also due to defects and terminations [ 49 , 50 , 51 ]. Monolayer MoS 2 shows a strong photoluminescence peak at 1.85–1.90 eV ( Figure 6 b red spectrum).…”
Section: Conformance Of Mono- or Few-layer Mos 2 W...mentioning
confidence: 99%